Is there a relation between stillbirth and low levels of vitamin D in the population? A bi-national follow-up study of vitamin D fortification - Pelle G. Lindqvist; Mika Gissler; Birgitta Essén (BMC Pregnancy and Childbirth, 2023)
Abstract Background Stillbirth has been associated with low plasma vitamin D. Both Sweden and Finland have a high proportion of low plasma vitamin D levels (< 50 nmol/L). We aimed to assess the odds of stillbirth in relation to changes in national vitamin D fortification. Methods We surveyed all pregnancies in Finland between 1994 and 2021 (n = 1,569,739) and Sweden (n = 2,800,730) with live or stillbirth registered in the Medical Birth Registries. The mean incidences before and after changes in the vitamin D food fortification programs in Finland (2003 and 2009) and Sweden (2018) were compared with cross-tabulation with 95% confidence intervals (CI). Results In Finland, the stillbirth rate declined from ~ 4.1/1000 prior to 2003, to 3.4/1000 between 2004 and 2009 (odds ratio [OR] 0.87, 95% CI 0.81–0.93), and to 2.8/1000 after 2010 (OR 0.84, 95% CI 0.78–0.91). In Sweden, the stillbirth rate decreased from 3.9/1000 between 2008 and 2017 to 3.2/1000 after 2018 (OR 0.83, 95% CI 0.78–0.89). When the level of the dose-dependent difference in Finland in a large sample with correct temporal associations decreased, it remained steady in Sweden, and vice versa, indicating that the effect may be due to vitamin D. These are observational findings that may not be causal. Conclusion Each increment of vitamin D fortification was associated with a 15% drop in stillbirths on a national level. If true, and if fortification reaches the entire population, it may represent a milestone in preventing stillbirths and reducing health inequalities.